Maxime Fulconis, Familles dominantes, réseaux de fidélités et pouvoir (Italie centrale, xie-xiiie siècles) - Maxime Fulconis (Perspectives Médiévales)
This thesis focuses on dominant families, both urban and rural, in central Italy during the 11th to 13th centuries. The prosopographical and sociological study of these various privileged groups also serves as an entry point to analyze power and its transformations, particularly important in a context of development of communal institutions and reconfiguration of lordships. Borrowing reading grids and methods from sociology, this work considers power as the conscious capacity of an actor to structure the field of action and thought of others and therefore analyzes all of the daily actions and techniques that elites deploy to establish, impose, legitimize and perpetuate economic, social or symbolic dominance. Thus, the investigation places relationships and networks – interpersonal, economic, informational – at the center of attention, as well as the relationships within and to space. It notably develops the concept of networks of fidelity, which accounts for all the ties that a powerful individual can establish to influence the actions of others. The study of these daily interpersonal relationships and their evolution sheds new light on the transformations of lordship or the political organization of cities and, more generally, on the transition from the society of the regnum italicum of Carolingian pattern to communal Italy. The analysis is based on the systematic examination of all written and material sources from Umbria and northern Latium, as well as the creation of a database and GIS. Special attention is devoted to lordship, for which a new definition is established, reflecting the diversity of its forms and its evolution over time. Through the precise and detailed study of the center of the Italian peninsula, this work also provides new insights into incastellamento, the evolution of family structures, the definition of lordship, tenure and fief, the concept of feudalism, the development of communes, and the debate between mutationism and antimutationism.